2017
DOI: 10.25135/acg.oc.18.17.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, in vitro antiproliferative and cytotoxicity effects of a new class of 2-((1R,2S)-2-((E)-4-substitutedstyryl) cyclooctyl)benzo[d]thiazole derivatives

Abstract: Abstract:The novel 2-((1R,2S)-2-((E)-4-substitutedstyryl) cyclooctyl)benzo [d]thiazoles (12-14) were synthesized from the reaction of 10-(4-substitutedbenzylidene)bicyclo[6.2.0]decan-9-ones (5a-8a) with 2-aminothiophenol (11) in the presence of p-TsOH at reflux conditions in good yields. The antiproliferative activities of 12-14 were determined againts C6 (rat brain carcinoma) and HeLa (human cervical carcinoma) cell lines using BrdU cell proliferation ELISA assay. 5-Fu (5-fluorouracil) was used as standard. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Therefore, the utilization of compounds that induce apoptosis is crucial in cancer treatment (Ceylan et al, 2020;Pfeffer & Singh, 2018;Uremis et al, 2017a;2017b). Although limited studies have demonstrated that CuD, CuI, and CuE induce apoptosis in HCC through apoptotic proteins, they have been reported to induce apoptosis in various cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the utilization of compounds that induce apoptosis is crucial in cancer treatment (Ceylan et al, 2020;Pfeffer & Singh, 2018;Uremis et al, 2017a;2017b). Although limited studies have demonstrated that CuD, CuI, and CuE induce apoptosis in HCC through apoptotic proteins, they have been reported to induce apoptosis in various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of cancer formation, damaged cells promote prolonged cell survival by genetic mutations, the release of apoptosis inhibitor proteins, and the expression of antiapoptotic proteins from the Bcl‐2 family, thereby increasing the continuity of the cell cycle. Therefore, the utilization of compounds that induce apoptosis is crucial in cancer treatment (Ceylan et al, 2020; Pfeffer & Singh, 2018; Uremis et al, 2017a; 2017b). Although limited studies have demonstrated that CuD, CuI, and CuE induce apoptosis in HCC through apoptotic proteins, they have been reported to induce apoptosis in various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported the in vitro cytotoxic evaluation of some cis‐ substituted 1,3‐benzothiazole derivatives against HeLa (Human Cervical Carcinoma Cells) and C6 (Rat Brain Tumor) cancer cells. Compounds showed high activity with IC 50 values ranging from IC 50 ≤5 μ m to IC 50 =9.53 μ m compared to 5‐FU (IC 50 ≤5 μ m ).…”
Section: Introductionmentioning
confidence: 99%
“…10 µL suspended cell was mixed with 10 µL trypan blue, then 10 µL of this mixture was pipetted to Thoma cell counting chamber to determine the cell concentration. The cell stock suspension was prepared into the 15 mL of falcon tube, then pippeted into the cell plates (5 ×10 3 cells/well) [35,36].…”
Section: Cell Cultures Preparationmentioning
confidence: 99%